MgH2 & multivalent titanium composite hydrogen storage material and large-scale preparation method
By adding titanium-based catalytic material to MgH2 to form a composite hydrogen storage material with multivalent titanium, the problem of slow hydrogen absorption and release of MgH2 is solved, and the effect of reducing the reaction energy barrier and improving the kinetic performance is achieved. It is suitable for large-scale production and application.
Patent Information
- Application Number
- CN202510042052.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The high hydrogen release enthalpy of MgH2 and the strong interaction between H-H bonds and Mg-H bonds lead to a slow hydrogen absorption and release reaction, making it difficult to directly use in large-scale production and applications.
MgH2 and multivalent titanium composite hydrogen storage material are used to add 3-7% titanium-based catalytic material, including magnesium powder and nanorutile phase titanium dioxide particles, to MgH2, to form a composite structure of titanium-based catalytic material and MgH2 to reduce the energy barrier for hydrogen absorption and release.
By increasing the contact area between the titanium-based catalytic material and MgH2 and changing the electronic state of the titanium dioxide particles, multivalent titanium is formed, which significantly reduces the energy barrier for hydrogen absorption and release, improves the kinetic performance and hydrogen absorption/discharge rate, making MgH2-based hydrogen storage materials suitable for large-scale production and application.
Smart Images

Figure BDA0005237242440000101 
Figure HDA0005237242460000011 
Figure HDA0005237242460000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a MgH2 & multivalent titanium composite hydrogen storage material and a large-scale preparation method thereof. Background Art
[0002] Hydrogen energy is expected to become the "ideal fuel" in the era of decarbonization, and the discovery, development and modification of high-performance hydrogen storage materials are the key to the future development of solid-state hydrogen storage and hydrogen energy utilization. Among them, magnesium-based hydrogen storage materials represented by MgH2 have many significant advantages. First, the low-cost Mg is extremely abundant in nature and easy to obtain. Secondly, MgH2 has a high reversible hydrogen absorption and desorption capacity of 7.6wt% and a hydrogen absorption capacity of 110kgH2 / m 3 High volumetric hydrogen storage density. Compared with other hydrogen storage methods, the volume of magnesium-based hydrogen storage materials is relatively small when storing the same mass of hydrogen, and has good application prospects.
[0003] However, the thermodynamics of MgH2 is very stable, with a dehydrogenation enthalpy ΔH of up to 75 kJ / molH2 and an entropy ΔS of 135 J / K / mol, which requires MgH2 to be above 280°C to release hydrogen under 0.1 MPa conditions; on the other hand, the interaction between the HH bond and the Mg-H bond is strong, making the dehydrogenation energy barrier of MgH2 as high as 145.08 kJ / mol, and the rate of hydrogen absorption and dehydrogenation is slow. Therefore, MgH2 is difficult to directly produce and apply on a large scale as a solid-state hydrogen storage material. MgH2 needs to be modified to reduce the energy barrier of the MgH2 hydrogen absorption and dehydrogenation reaction, accelerate its kinetics, and achieve a significant enhancement of hydrogen storage performance while retaining the capacity to the maximum extent. Summary of the invention
[0004] In order to reduce the energy barrier of hydrogen absorption and desorption reactions of magnesium-based hydrogen storage materials and realize large-scale production and application of magnesium-based hydrogen storage materials, the present application provides a MgH2&multivalent titanium composite hydrogen storage material and a large-scale preparation method.
[0005] In the first aspect, the present application provides a MgH2 & multivalent titanium composite hydrogen storage material, which adopts the following technical solution:
[0006] A MgH2&multivalent titanium composite hydrogen storage material comprises the following raw materials in weight percentage: 3-7% of a titanium-based catalytic material and 93-97% of MgH2, wherein the titanium-based catalytic material comprises magnesium powder and nano-rutile phase titanium dioxide particles in a mass ratio of 1:(0.9-1.2).
[0007] By adopting the above technical scheme, the nano-rutile phase titanium dioxide particles in the titanium-based catalytic material have good catalytic activity and high specific surface area, can provide abundant active sites, increase the contact area between the titanium-based catalytic material and MgH2, can effectively promote the adsorption and dissociation of hydrogen molecules, thereby reducing the activation energy of the reaction, making the absorption and desorption of hydrogen reactions easier to carry out. There is a synergistic effect between magnesium powder and nano-rutile phase titanium dioxide particles. The magnesium powder changes the electronic state of the surface of the titanium dioxide particles, so that the titanium-based catalytic material contains Ti in multiple valence states, which enhances the activity of the titanium-based catalytic material. The above raw material ratio helps the titanium-based catalytic material to be evenly dispersed in MgH2, thereby forming an effective catalytic network in the MgH2 matrix, which can not only accelerate the absorption and desorption of hydrogen reactions, but also make the reaction more uniform and efficient. Moreover, the amount of titanium-based catalytic material can be reduced while ensuring the catalytic effect, which helps to reduce the production cost of hydrogen storage materials. Therefore, the MgH2&multivalent titanium composite hydrogen storage material formed by the titanium-based catalytic material and MgH2 reduces the energy barrier of the hydrogen absorption and desorption reaction, improves the kinetic performance, and helps to increase the hydrogen absorption / desorption rate, thereby realizing the large-scale production and application of magnesium-based hydrogen storage materials.
[0008] In a specific embodiment, the average particle size of the nano-rutile phase titanium dioxide particles is 50-70 nm.
[0009] By adopting the above technical solution, nano-rutile phase titanium dioxide particles have a higher specific surface area within the particle size range of 50-70nm, which can increase the contact area with MgH2. In addition, nano-scale particles are conducive to the adsorption and dissociation of hydrogen molecules, accelerating the kinetic process of hydrogen absorption and desorption reactions. The above particle size also helps the particles to be evenly distributed in the composite material, further optimizing the hydrogen storage performance.
[0010] In the second aspect, the present application provides a large-scale preparation method of a MgH2 & multivalent titanium composite hydrogen storage material, which adopts the following technical solution:
[0011] A large-scale preparation method of MgH2 & multivalent titanium composite hydrogen storage material comprises the following steps:
[0012] In an argon environment of 9.5-10.5 Pa, magnesium powder is heated to 680-750°C to melt to obtain magnesium water;
[0013] Mixing magnesium water and nano-rutile titanium dioxide particles, heating to 1300° C., and reacting for 60-120 minutes to obtain a reaction solution;
[0014] Cooling the reaction solution to room temperature to obtain a titanium-based catalytic material;
[0015] The titanium-based catalytic material is mixed with MgH2 and subjected to ball milling treatment to obtain a MgH2 & multivalent titanium composite hydrogen storage material.
[0016] By adopting the above technical solution, at a high temperature of 1300°C, magnesium water promotes the phase change of titanium dioxide in the nano-rutile phase titanium dioxide particles to form a more catalytically active phase. At the same time, magnesium powder undergoes electron transfer or chemical bonding with titanium dioxide during the high-temperature reaction process to generate a titanium-based catalytic material containing multiple valence states of Ti. The titanium-based catalytic material and MgH2 can be evenly dispersed on a microscopic scale by ball milling. This dispersion not only enhances the interfacial contact between the titanium-based catalytic material and MgH2, but also optimizes the mass transfer path during the hydrogen storage process, so that hydrogen molecules can interact with the catalytic sites more efficiently. Therefore, the MgH2 & multivalent titanium composite hydrogen storage material prepared by the above method has a lower hydrogen absorption and desorption reaction energy barrier, a higher hydrogen absorption / desorption rate, and is convenient for large-scale production and application.
[0017] In a specific embodiment, the nano-rutile phase titanium dioxide particles are prepared according to the following steps:
[0018] Mixing a TiCl3 ethanol solution having a mass concentration of 15% with water in a volume ratio of 1:(4-6) to obtain a mixed solution;
[0019] The mixed solution is reacted at 120-150° C. with stirring for 40-55 hours, and then centrifuged, washed, and dried to obtain nano-rutile phase titanium dioxide particles.
[0020] By adopting the above technical solution, the volume ratio of TiCl3 ethanol solution to water and the reaction conditions are adjusted to the above range, and the particle size of the titanium dioxide particles can be adjusted to the nanometer level and have a rutile phase structure. This structure has high catalytic activity and stability, and can effectively improve the performance of hydrogen storage materials. Through centrifugation, washing, drying and other steps, impurities and unreacted products on the surface of the particles can be removed to ensure the purity and dispersibility of the particles. Using this preparation method, large-scale production of nano-rutile phase titanium dioxide particles can also be achieved, providing strong support for the large-scale application of MgH2 & multivalent titanium composite hydrogen storage materials.
[0021] In a specific embodiment, polystyrene microspheres are added to the mixed solution, and then reacted at 120-150°C with stirring for 40-55 hours, centrifuged, washed, and dried, and the dried product is calcined at 500-600°C for 3-5 hours to obtain nano-rutile phase titanium dioxide particles with a porous structure.
[0022] By adopting the above technical solution, the polystyrene microspheres have a specific pore size and structure. During the reaction process, they are mixed in the product. After calcination at 500-600°C, the polystyrene microspheres are backed out, thereby introducing a porous structure into the nano-rutile phase titanium dioxide particles. The porous nano-rutile phase titanium dioxide particles have a higher specific surface area, which helps to provide more active sites, so that the titanium-based catalytic material can contact and react with hydrogen molecules more fully, enhance the catalytic efficiency of the titanium-based catalytic material, and make the hydrogen absorption and desorption reaction more rapid and efficient. Moreover, the porous structure is conducive to the diffusion and transmission of hydrogen. In the process of hydrogen storage, hydrogen needs to enter and leave the material quickly. The porous structure provides more channels and larger space for hydrogen, thereby accelerating the diffusion rate of hydrogen and increasing the rate of hydrogen storage and desorption.
[0023] In a specific implementation scheme, magnesium water and nano-rutile phase titanium dioxide particles are mixed, ammonia gas is introduced, the temperature is raised to 1300° C., and the reaction is carried out for 60-120 minutes to obtain a reaction liquid; while the ammonia gas is kept introduced into the reaction liquid, the reaction liquid is cooled to room temperature to obtain a titanium-based catalytic material with a porous structure.
[0024] By adopting the above technical solution, ammonia is introduced and reacted at high temperature, and ammonia will decompose, which helps to form a porous structure in the titanium-based catalytic material. The porous structure not only increases the specific surface area of the material, but also provides more channels and spaces for the adsorption and desorption of hydrogen, thereby accelerating the process of hydrogen storage and release.
[0025] In a specific embodiment, the ball milling speed of the ball milling treatment is 350-400 rpm and the ball milling time is 7-9 h.
[0026] By adopting the above technical solution, the appropriate ball milling speed and time can ensure that the material is fully ground and mixed, so that MgH2 and multivalent titanium can be more evenly dispersed in the composite material. This uniform dispersion is conducive to improving the hydrogen absorption and desorption performance of the hydrogen storage material, making it more efficient and stable. By controlling the ball milling speed and time within the above range, the present application can avoid material structure damage or performance degradation caused by excessive grinding, maintain the integrity and stability of the material, and optimize its hydrogen storage performance.
[0027] In summary, this application has the following beneficial effects:
[0028] 1. The MgH2 & multivalent titanium composite hydrogen storage material prepared in the present application has a lower energy barrier for hydrogen absorption and desorption reactions and a higher hydrogen absorption / desorption rate, and is convenient for large-scale production and application.
[0029] 2. In the present application, nano-rutile titanium dioxide particles with an average particle size of 50-70 nm are preferably used, which can increase the contact area with MgH2, help the adsorption and dissociation of hydrogen molecules, and accelerate the kinetic process of hydrogen absorption and desorption reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the XRD spectrum of the nano-rutile phase titanium dioxide particles prepared in Example 1.
[0031] Figure 2 This is the XRD diffraction pattern of the titanium-based catalytic material prepared in Example 1.
[0032] Figure 3 It is a curve diagram of the dehydrogenation amount (wt %) of the composite hydrogen storage materials prepared in Example 1 and Comparative Examples 1-2 in the range of 100-500°C.
[0033] Figure 4 It is a curve diagram of the hydrogen absorption amount (wt%) of the composite hydrogen storage material prepared in Example 1 at 140° C., 180° C. and 200° C. in the range of 0-12 min.
[0034] Figure 5 It is a curve diagram of the hydrogen release amount (wt %) of the composite hydrogen storage material prepared in Example 1 at 220° C., 270° C. and 300° C. in the range of 0-100 min. DETAILED DESCRIPTION
[0035] The following is combined with Figure 1-5 , Examples and Comparative Examples further illustrate the present application in detail.
[0036] Example
[0037] Example 1
[0038] This embodiment provides a MgH2&multivalent titanium composite hydrogen storage material, comprising the following raw materials in weight percentage: 5% titanium-based catalytic material and 95% MgH2. The titanium-based catalytic material comprises magnesium powder and nano-rutile phase titanium dioxide particles in a mass ratio of 1:1. The average particle size of the nano-rutile phase titanium dioxide particles is 60nm.
[0039] This embodiment also provides a large-scale preparation method of MgH2 & multivalent titanium composite hydrogen storage material, comprising the following steps:
[0040] A TiCl3 ethanol solution with a mass concentration of 15% was mixed with water in a volume ratio of 1:5 to obtain a mixed solution. The mixed solution was heated to 135°C, maintained at the temperature and stirred for 48 hours, and then naturally cooled to room temperature. The product was centrifuged, washed with ultrapure water, dried at 80°C for 2 hours, and sieved to obtain nano-rutile phase titanium dioxide particles with an average particle size of 60nm.
[0041] Put magnesium powder into a crucible in a medium frequency induction melting furnace, fill it with 0.5MPa argon gas, remove the air in the medium frequency induction melting furnace, then evacuate the medium frequency induction melting furnace to 10pa, heat the crucible to 700℃, completely melt the magnesium powder in the crucible, and obtain magnesium water.
[0042] Nano-rutile titanium dioxide particles were added into the crucible in proportion using a secondary feeding device. The magnesium water and the nano-rutile titanium dioxide particles were mixed, and then the temperature was raised to 1300° C. and reacted for 90 minutes to obtain a reaction solution.
[0043] The reaction solution was poured onto a water cooling plate and cooled to room temperature to obtain a titanium-based catalytic material.
[0044] The titanium-based catalytic material and MgH2 were mixed in proportion and subjected to ball milling treatment at a ball milling speed of 380 rpm and a ball milling time of 8 h to obtain a MgH2 & multivalent titanium composite hydrogen storage material.
[0045] Example 2
[0046] The only difference between this embodiment and embodiment 1 is that the MgH2 & multivalent titanium composite hydrogen storage material includes the following raw materials in weight percentage: 3% titanium-based catalytic material and 97% MgH2.
[0047] Example 3
[0048] The only difference between this embodiment and embodiment 1 is that the MgH2 & multivalent titanium composite hydrogen storage material includes the following raw materials in weight percentage: 7% titanium-based catalytic material and 93% MgH2.
[0049] Example 4
[0050] The only difference between this embodiment and embodiment 1 is that the titanium-based catalytic material includes magnesium powder and nano-rutile phase titanium dioxide particles in a mass ratio of 1:0.9.
[0051] Example 5
[0052] The only difference between this embodiment and embodiment 1 is that the titanium-based catalytic material includes magnesium powder and nano-rutile phase titanium dioxide particles in a mass ratio of 1:1.2.
[0053] Example 6
[0054] The difference between this embodiment and embodiment 1 is that the average particle size of the nano-rutile phase titanium dioxide particles is 50 nm. In the large-scale preparation method of the MgH2 & multivalent titanium composite hydrogen storage material, the nano-rutile phase titanium dioxide particles with an average particle size of 50 nm are obtained by sieving.
[0055] Example 7
[0056] The difference between this embodiment and embodiment 1 is that the average particle size of the nano-rutile phase titanium dioxide particles is 70 nm. In the large-scale preparation method of the MgH2 & multivalent titanium composite hydrogen storage material, the nano-rutile phase titanium dioxide particles with an average particle size of 70 nm are obtained by sieving.
[0057] Example 8
[0058] The difference between this embodiment and embodiment 1 is that in the large-scale preparation method of MgH2 & multivalent titanium composite hydrogen storage material, a TiCl3 ethanol solution with a mass concentration of 15% is mixed with water in a volume ratio of 1:4 to obtain a mixed solution. The mixed solution is heated to 150°C, maintained at the temperature and stirred for 40 hours, and then naturally cooled to room temperature.
[0059] Example 9
[0060] The difference between this embodiment and embodiment 1 is that in the large-scale preparation method of MgH2 & multivalent titanium composite hydrogen storage material, a TiCl3 ethanol solution with a mass concentration of 15% is mixed with water in a volume ratio of 1:6 to obtain a mixed solution. The mixed solution is heated to 120°C, maintained at the temperature and stirred for 55 hours, and then naturally cooled to room temperature.
[0061] Example 10
[0062] The difference between this embodiment and embodiment 1 is that in the large-scale preparation method of MgH2 & multivalent titanium composite hydrogen storage material, a TiCl3 ethanol solution with a mass concentration of 15% is mixed with water in a volume ratio of 1:5 to obtain a mixed solution. Polystyrene microspheres are added to the mixed solution, and the mass ratio of polystyrene microspheres to the mixed solution is 3:100. The mixed solution is then heated to 135°C, maintained at temperature and stirred, reacted for 48 hours, and then naturally cooled to room temperature. The product is centrifuged, washed with ultrapure water, and then dried at 80°C for 2 hours, and then the dried product is placed in a muffle furnace, heated to 550°C, and calcined for 4 hours. After naturally cooling to room temperature, the calcined product is sieved to obtain nano-rutile phase titanium dioxide particles with an average particle size of 60nm and a porous structure.
[0063] Embodiment 11
[0064] The only difference between this embodiment and embodiment 10 is that in the large-scale preparation method of MgH2 & multivalent titanium composite hydrogen storage material, the dried product is placed in a muffle furnace, heated to 500°C, and then calcined for 5 hours.
[0065] Example 12
[0066] The only difference between this embodiment and embodiment 10 is that in the large-scale preparation method of MgH2 & multivalent titanium composite hydrogen storage material, the dried product is placed in a muffle furnace, heated to 600°C, and then calcined for 3 hours.
[0067] Example 13
[0068] The difference between this embodiment and embodiment 1 is that in the large-scale preparation method of MgH2&multivalent titanium composite hydrogen storage material, nano rutile phase titanium dioxide particles are added to the crucible in proportion using a secondary feeding device, magnesium water and nano rutile phase titanium dioxide particles are mixed, and at the same time, ammonia is introduced into the medium frequency induction melting furnace, argon in the medium frequency induction melting furnace is removed, and then the medium frequency induction melting furnace is evacuated to 10Pa, and then the temperature is raised to 1300°C, and the reaction is carried out for 90 minutes to obtain a reaction liquid. The reaction liquid is poured onto a water cooling plate, and the reaction liquid is cooled to room temperature while ammonia is kept introduced into the reaction liquid to obtain a titanium-based catalytic material with a porous structure.
[0069] Embodiment 14
[0070] The only difference between this embodiment and Embodiment 1 is that in the large-scale preparation method of MgH2 & multivalent titanium composite hydrogen storage material, the titanium-based catalytic material and MgH2 are mixed in proportion and ball-milled at a ball-milling speed of 350 rpm and a ball-milling time of 9 h to obtain the MgH2 & multivalent titanium composite hydrogen storage material.
[0071] Embodiment 15
[0072] The only difference between this embodiment and Embodiment 1 is that in the large-scale preparation method of MgH2 & multivalent titanium composite hydrogen storage material, the titanium-based catalytic material and MgH2 are mixed in proportion and ball-milled at a ball-milling speed of 350 rpm and a ball-milling time of 9 h to obtain the MgH2 & multivalent titanium composite hydrogen storage material.
[0073] Comparative Example
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 1 is that the composite hydrogen storage material of this comparative example includes the following raw materials in weight percentage: 5% of nano-rutile phase titanium dioxide particles and 95% of MgH2. In the large-scale preparation method of the composite hydrogen storage material, an equal amount of nano-rutile phase titanium dioxide particles is used to replace the titanium-based catalytic material.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 1 is that the composite hydrogen storage material of this comparative example includes the following raw materials in weight percentage: 100% MgH2. In the large-scale preparation method of the composite hydrogen storage material, an equal amount of MgH2 is used to replace the titanium-based catalytic material.
[0078] Performance testing
[0079] The following performance tests were performed on the composite hydrogen storage materials prepared in Examples 1-15 and Comparative Examples 1-2:
[0080] The nano-rutile phase titanium dioxide particles and titanium-based catalytic materials prepared in Example 1 were tested using a TD-3500 X-ray diffractometer. The results are as follows: Figure 1 and Figure 2 shown.
[0081] The dehydrogenation amount (wt%) of the composite hydrogen storage materials prepared in Example 1 and Comparative Examples 1-2 in the range of 100-500°C was tested, and the data curves are as follows: Figure 3 shown.
[0082] The hydrogen absorption (wt%) of the composite hydrogen storage material prepared in Example 1 was tested at 140°C, 180°C and 200°C in the range of 0-12 min. The data curves are shown in FIG. Figure 4 shown.
[0083] The amount of hydrogen released (wt%) of the composite hydrogen storage material prepared in Example 1 was tested at 220°C, 270°C and 300°C in the range of 0-100 min. The data curves are shown in FIG. Figure 5 shown.
[0084] The hydrogen absorption amount of the composite hydrogen storage materials prepared in Examples 1-15 and Comparative Examples 1-2 in the 10th minute at 140°C and the hydrogen release amount (wt %) in the 100th minute at 300°C are shown in Table 1.
[0085] Table 1
[0086]
[0087] Combined with Example 1 and Figure 1-2 It can be seen that the preparation method of Example 1 obtains rutile-phase nano-titanium dioxide particles and titanium-based catalytic materials containing Ti in various valence states.
[0088] Combined with Example 1 and Comparative Examples 1-2 and Figure 3It can be seen that compared with Example 1, within 350°C, the absolute values of the dehydrogenation amounts of Comparative Examples 1-2 in the range of 100-500°C are all smaller. In the case of more than 400°C, the absolute values of the dehydrogenation amounts of Comparative Examples 1-2 in the range of 100-500°C are all larger. This shows that the use of the raw material ratio and preparation method of Example 1 is helpful to reduce the activation energy of the hydrogen storage material reaction and the energy barrier of the hydrogen absorption and desorption reaction.
[0089] From Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that compared with Example 1, the absolute value of the hydrogen absorption amount of the composite hydrogen storage material of Comparative Examples 1-2 at 140°C in the 10th minute and the absolute value of the hydrogen release amount at 300°C in the 100th minute are both smaller, which indicates that the raw material ratio and preparation method of Example 1 are helpful to improve the hydrogen absorption / desorption rate of the hydrogen storage material.
[0090] Combined with Example 1 and Figure 4-5 It can be seen that the composite hydrogen storage material prepared by the raw material ratio and preparation method of Example 1 has the fastest hydrogen absorption rate and the highest absolute value of hydrogen absorption at 140°C; and the fastest hydrogen release rate and the highest absolute value of hydrogen release at 300°C.
[0091] Combining Examples 1-15 and Comparative Examples 1-2 and Table 1, it can be seen that the amount of hydrogen absorbed by the composite hydrogen storage material of Examples 1-15 in the 10th minute at 140°C and the amount of hydrogen released in the 100th minute at 300°C are both large, and significantly greater than Comparative Examples 1-2. Moreover, the detection values of Examples 10-13 are significantly greater than the detection values of Example 1. This shows that the raw material ratios and preparation methods of Examples 1-15 can produce composite hydrogen storage materials with low hydrogen absorption and desorption reaction energy barriers and fast hydrogen absorption / desorption rates. Moreover, the composite hydrogen storage material produced by the preparation method of Examples 10-13 has better performance.
[0092] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A MgH2 & multivalent titanium composite hydrogen storage material, characterized in that: The raw materials include the following weight percentages: 3-7% of titanium-based catalytic material and 93-97% of MgH2, wherein the titanium-based catalytic material includes magnesium powder and nano-rutile phase titanium dioxide particles in a mass ratio of 1:(0.9-1.2).
2. The MgH2 & multivalent titanium composite hydrogen storage material according to claim 1, characterized in that: The average particle size of the nano-rutile phase titanium dioxide particles is 50-70 nm.
3. A large-scale preparation method of the MgH2 & multivalent titanium composite hydrogen storage material according to any one of claims 1 or 2, characterized in that: The steps include: In an argon environment of 9.5-10.5 Pa, magnesium powder is heated to 680-750°C to melt to obtain magnesium water; Mixing magnesium water and nano-rutile titanium dioxide particles, heating to 1300° C., and reacting for 60-120 minutes to obtain a reaction solution; Cooling the reaction solution to room temperature to obtain a titanium-based catalytic material; The titanium-based catalytic material is mixed with MgH2 and subjected to ball milling treatment to obtain a MgH2 & multivalent titanium composite hydrogen storage material.
4. The large-scale preparation method of a MgH2 & multivalent titanium composite hydrogen storage material according to claim 3, characterized in that: The nano-rutile phase titanium dioxide particles are prepared according to the following steps: Mixing a TiCl3 ethanol solution having a mass concentration of 15% with water in a volume ratio of 1:(4-6) to obtain a mixed solution; The mixed solution is reacted at 120-150° C. with stirring for 40-55 hours, and then centrifuged, washed, and dried to obtain nano-rutile phase titanium dioxide particles.
5. The large-scale preparation method of a MgH2 & multivalent titanium composite hydrogen storage material according to claim 3, characterized in that: Add polystyrene microspheres to the mixed solution, react at 120-150° C. with stirring for 40-55 hours, centrifuge, wash and dry, and calcine the dried product at 500-600° C. for 3-5 hours to obtain nano-rutile phase titanium dioxide particles with a porous structure.
6. The large-scale preparation method of a MgH2 & multivalent titanium composite hydrogen storage material according to claim 3, characterized in that: Mix magnesium water and nano-rutile titanium dioxide particles, introduce ammonia, heat to 1300°C, react for 60-120 minutes to obtain a reaction liquid; keep introducing ammonia into the reaction liquid, cool the reaction liquid to room temperature to obtain a titanium-based catalytic material with a porous structure.
7. The large-scale preparation method of a MgH2 & multivalent titanium composite hydrogen storage material according to claim 3, characterized in that: The ball milling speed of the ball milling treatment is 350-400 rpm and the ball milling time is 7-9 hours.
Citation Information
Patent Citations
Titanium-containing substance catalytic modified magnesium-based hydrogen storage material as well as preparation method and application thereof
CN114620676A
TiO2-based catalyst as well as preparation method and application thereof
CN116493030A
Preparation of rutile-phase titanium dioxide porous microspheres and application of rutile-phase titanium dioxide porous microspheres in sodium-ion battery
CN117199332A
Magnesium-based hydrogen storage material and preparation method thereof
CN117430082A
Modified catalyst and application thereof in modification of aluminum hydride hydrogen storage system
CN117504918A
Cited By
Composite hydrogen storage material and preparation method thereof
CN121158730A